AGENT-BASED SPATIAL MODELING OF THE DISTRIBUTION AND IMPACT OF VACCINATION AND REGULATIONS ON THE SPREAD OF COMMUNICABLE DISEASES IN THE FACULTY STEI ITB AREA - Faturrahman, Vegi
COVID-19 is an infectious disease that emerged in 2020 and has brought about numerous negative impacts, altering social norms, especially in the context of teaching and learning on campus. Preventive measures have been implemented to curb the spread of the virus, including vaccination campaigns and protocols to restrict movement. By getting vaccinated, individuals can increase their immunity and reduce the risk of transmission. It is crucial to ensure the vaccine's effectiveness to control the spread of COVID-19. Additionally, enforcing movement restrictions is essential to maintain the continuity of teaching and learning while minimizing the negative impact on people's health. The utilization and enforcement of COVID-19 vaccines can be analyzed through modeling to help predict the spread of the virus. There are various types of modeling, including agent-based modeling, which can provide an overview of how individuals in a system behave after specific actions are taken. Spatial data can be incorporated to create a more accurate representation of the location when modeling is performed. This research aims to use agent-based spatial modeling to